The Gain of Performance of Optical WDM Networks. (17th March 2008) - Bahleda, Miroslav; Blunar, Karol
Abstract : We study the blocking probability and performance of single-fiber and multifiber optical networks with wavelength division multiplexing (WDM). We extend the well-known analytical blocking probability model by Barry and Humblet to the general model, which is proposed for both single-fiber and multifiber network paths with any kind of wavelength conversion (no, limited, or full wavelength conversion) and for uniform and nonuniform link loads. We investigate the effect of the link load, wavelength conversion degree, and the number of wavelengths, fibers, and hops on blocking probability. We also extend the definition of the gain of wavelength conversion by Barry and Humblet to the gain of performance, which is fully general. Thanks to this definition and implementation of our model, we compare different WDM node architectures and present interesting results.